Caries management pathways preserve dental tissues and promote oral health. Issue 1 (25th January 2013) - Ismail, Amid I.; Tellez, Marisol; Pitts, Nigel B.; Ekstrand, Kim R.; Ricketts, David; Longbottom, Christopher; Eggertsson, Hafsteinn; Deery, Christopher; Fisher, Julian; Young, Douglas A.; Featherstone, John D. B.; Evans, Wendell; et al.
Abstract In May 2012, cariologists, dentists, representatives of dental organizations, manufacturers, and third party payers from several countries, met in Philadelphia, Pennsylvania, to define a common mission; goals and strategic approaches for caries management in the 21th century. The workshop started with an address by Mr. Stanley Bergman, CEO of Henry Schein Inc. which focused on the imperative for change in academia, clinical practice, and public health. For decades, new scientific evidence on caries and how it should be managed have been discussed among experts in the field. However, there has been some limited change, except in some Scandinavian countries, in the models of caries management and reimbursement which have been heavily skewed toward 'drilling and filling'. There is no overall agreement on a caries' case definition or on when to surgically intervene. The participants in the workshop defined a new mission for all caries management approaches, both conventional and new. The mission of each system should be to preserve the tooth structure, and restore only when necessary. This mission marks a pivotal line for judging when to surgically intervene and when to arrest or remineralize early noncavitated lesions. Even when restorative care is necessary, the removal of hard tissues should be lesion‐focused and aim to preserve, as much as possible, sound tooth structure. Continuing management of the etiological factors of caries and the use of science‐based preventive regimens also will be required to prevent recurrence and re‐restoration. These changes have been debated for over a decade. The Caries Management Pathways includes all systems and philosophies, conventional and new, of caries management that can be used or modified to achieve the new mission. The choice of which system to use to achieve the mission of caries management is left to the users and should be based on the science supporting each approach or philosophy, experience, utility, and ease of use. This document also presents a new 'Caries Management Cycle' that should be followed regardless of which approach is adopted for caries prevention, detection, diagnosis, and treatment. To aid success in the adoption of the new mission, a new reimbursement system that third party payers may utilize is proposed (for use by countries other than Scandinavian countries or other countries where such systems already exist). The new reimbursement/incentive model focuses on the mission of preservation of tooth structure and outcomes of caries management. Also described, is a research agenda to revitalize research on the most important and prevalent world‐wide human disease. The alliance of major dental organizations and experts that started in Philadelphia will hopefully propel over the next months and years, a change in how caries is managed by dentists all over the world. A new mission has been defined and it is time for all oral health professionals to focus on the promotion of oral health and preservation of sound teeth rather than counting the number of surgical restorative procedures provided.